The Impact of Emotional Intelligence on The Quality of Life from The Point of View of Teachers in Educational Institutions in Jordan - Al-Qaisi , Marwa Ibrahim (Journal of Posthumanism, 2025)
The current study aimed to identify the role of administrative creativity in the performance of teachers in public schools in the Irbid governorate, and to achieve the objectives of the current study, the descriptive analytical approach was used for its suitability to the type of study, where a questionnaire was developed to collect data from the sample that was chosen randomly from the study population of teachers in the governorate of Irbid, based on a sample of (250) male and female teachers. The questionnaire was sent and applied electronically, and (230) questionnaires were retrieved, i.e. (92%) of the total study sample, all of which are suitable for statistical analysis. The study also recommended the need to prepare training programs to develop administrative creativity among employees working in public schools and to create an appropriate environment for all employees working in public schools to help them create, develop, innovate, and take initiative The results of the study showed that there is a statistically significant effect of emotional intelligence on the quality of life represented by its three dimensions (social relations, work environment, stability, and job security), which indicates the existence of a correlation between emotional intelligence and quality of life in educational institutions in Jordan.